Annotated checklist, distribution, and taxonomic bibliography of the mosquitoes (Insecta: Diptera: Culicidae) of Argentina - Rossi, Gustavo Carlos (2015)
A decade and a half have passed since the last publication of the mosquito distribution list in Argentina. During this time several new records have been added, and taxonomic modifications have occurred at the genus and subgenus level. Therefore, considering these changes, I decided to create an updated list of the 242 species present in Argentina, along with their distributions by province. Two first records for Argentina (Culex lopesi and Cx. vaxus), two old records unregistered by authors (Cx. albinensis and Wyeomyia fuscipes), 13 new provincial records for 11 species (Cx. apicinus, Cx. bidens, Cx. eduardoi, Cx. lahillei, Cx. pipiens, Cx. tatoi, Cx. usquatus, Cx. imitator, Cx. oedipus, Sabethes chloropterus, and Wy. oblita), and the extension of distribution of other species are presented. The list of literature references for the documents concerning mosquitos is included.